Clinical Outcomes of Living-Donor Kidney Transplants with Multiple Renal Arteries Compared to Single Renal Artery: A Systematic Review and Meta-Analysis - Aqshal Radiva Eryadana; Eriawan Agung Nugroho; Muhammad Kemal Thariq Ibrahim; Pande Made Wisnu Tirtayasa; Ardy Santosa; Mohamad Adi Soedarso; Nanda Daniswara; Sofyan Rais Addin; Dimas Sindhu Wibisono; Fandy Wicaksono; Donny Austine Wibisisono (OBM Transplantation, 2026)
Multiple renal arteries in living-donor kidney transplantation create technical challenges, but their effect on clinical outcomes is unclear. This review assessed whether grafts with multiple renal arteries differ in short-term outcomes compared with single renal artery grafts. Following PRISMA 2020 guidelines and PROSPERO registration, a systematic search of PubMed, Embase, Scopus, Web of Science, and Cochrane CENTRAL was conducted from database inception until 31 October 2025. Studies published from January 2020 to 31 October 2025 that met the eligibility criteria were included to capture contemporary living-donor kidney transplantation practice. Comparative studies of adult living-donor kidney transplant recipients receiving multiple renal arteries versus single renal artery grafts were included. Primary outcomes were delayed graft function, 1-year graft and patient survival, and 12-month estimated glomerular filtration rate. Secondary outcomes included vascular and urological complications. Random-effects meta-analyses were performed, and certainty of evidence was assessed using GRADE. Ten studies (≈2,105 recipients; ≈600 MRA, ≈1,500 SRA) met inclusion criteria. However, only a limited subset of studies contributed to individual quantitative analyses, with three studies available for delayed graft function analysis and four studies for graft survival and estimated glomerular filtration rate outcomes. Multiple renal arteries were not associated with increased delayed graft function (RR 1.23; 95% CI 0.24-6.22) or inferior 1-year graft survival (RR 1.03; 95% CI 0.51-2.07). The interpretation of pooled estimates is limited by the small number of contributing studies, low event rates, and imprecision of confidence intervals. Living-donor kidney transplantation using grafts with multiple renal arteries appears to have comparable short-term outcomes to single-renal-artery grafts; however, the available evidence remains limited by the small number of comparative studies, retrospective designs, and imprecision of pooled estimates. Further large-scale prospective studies are required to confirm these findings.